The impact of mechanism on the management and outcome of penetrating colonic trauma - Oosthuizen, GV (Ann R Coll Surg Engl, 2018)
INTRODUCTION: In light of continuing controversy surrounding the management of penetrating colonic injuries, we set out to compare the outcome of penetrating colonic trauma according to whether the mechanism of injury was a stab wound or a gunshot wound. METHODS: Our trauma registry was interrogated for the 5-year period from January 2012 to December 2016. All patients over the age of 18 years with penetrating trauma (stab or gunshot) and with intraoperatively proven colonic injury were reviewed. Details of the colonic and concurrent abdominal injuries were recorded, together with the operative management strategy. In-hospital morbidities were divided into colon-related and non-colon related morbidities. The length of hospital stay and mortality were recorded. Direct comparison was made between patients with stab wounds and gunshot wounds to the colon. RESULTS: During the 5-year study period, 257 patients sustained a colonic injury secondary to penetrating trauma; 95% (244/257) were male and the mean age was 30 years. A total of 113 (44%) sustained a gunshot wound and the remaining 56% (144/257) sustained a stab wound. Some 88% (226/257) of all patients sustained a single colonic injury, while 12% (31/257) sustained more than one colonic injury. A total of 294 colonic injuries were found at laparotomy. Multiple colonic injuries were less commonly encountered in stab wounds (6%, 9/144 vs. 19%, 22/113, P < 0.001). Primary repair was more commonly performed for stab wounds compared with gunshot wounds (118/144 vs. 59/113, P < 0.001). Patients with gunshot wounds were more likely to need admission to intensive care, more likely to experience anastomotic failure, and had higher mortality. CONCLUSIONS: It would appear that colonic stab wounds and colonic gunshot wounds are different in terms of severity of the injury and in terms of outcome. While primary repair is almost always applicable to the management of colonic stab wounds, the same cannot be said for colonic gunshot wounds. The management of colonic gunshot wounds should be examined separately from that of stab wounds.